Recovery from Emotion Recognition Impairment after Temporal Lobectomy - Benuzzi, Francesca; Zamboni, Giovanna; Meletti, Stefano; Serafini, Marco; Lui, Fausta; Baraldi, Patrizia; Duzzi, Davide; Rubboli, Guido; Tassinari, Carlo Alberto; Nichelli, Paolo Frigio (Frontiers in Neurology, 2014)
Mesial temporal lobe epilepsy (MTLE) can be associated with emotion recognition impairment that can be particularly severe in patients with early onset seizures (1-3). Whereas there is growing evidence that memory and language can improve in seizure-free patients after anterior temporal lobectomy (ATL) (4), the effects of surgery on emotional processing are still unknown. We used functional magnetic resonance imaging (fMRI) to investigate short-term reorganization of networks engaged in facial emotion recognition in MTLE patients. Behavioral and fMRI data were collected from six patients before and after ATL. During the fMRI scan, patients were asked to make a gender decision on fearful and neutral faces. Behavioral data demonstrated that two patients with early-onset right MTLE were impaired in fear recognition while fMRI results showed they lacked specific activations for fearful faces. Post-ATL behavioral data showed improved emotion recognition ability, while fMRI demonstrated the recruitment of a functional network for fearful face processing. Our results suggest that ATL elicited brain plasticity mechanisms allowing behavioral and fMRI improvement in emotion recognition.